Self-reported sexually transmitted infection testing behaviour amongst incarcerated young male offenders: findings from a qualitative study. Issue 1 (1st January 2010) - Buston, Katie; Wight, Daniel
Abstract : Introduction: Sexually transmitted infections (STIs) are a major public health problem in the UK. Here we describe young men's self-reported STI testing behaviour, and explore why testing is and is not sought in two locales: the community and the Young Offender Institute (YOI). Methods: In-depth interviews were conducted with 40 men, aged 16–20 years, whilst incarcerated in a Scottish YOI. The participants were purposively sampled using answers from a questionnaire administered to 67 inmates. Results: The majority ( n = 24) of those interviewed reported having undergone STI testing: eight in the community, 12 within the YOI, and four in both the community and the YOI. The extent to which they were worried about STIs and perceived themselves 'at risk' was important in understanding openness to testing. The convenience of testing within the YOI boosted the numbers seeking testing once incarcerated. Not getting tested in the YOI was due to not realising that it was available or not getting around to it rather than objecting to, or being embarrassed about, testing. Discussion: Increasing awareness of the availability of STI testing within YOIs would be likely to result in higher uptake. An opt-out YOI STI screening programme would probably result in very high testing rates. Accessibility and convenience are key elements of testing procedures for this group, in both the YOI and community settings.